2019
DOI: 10.1155/2019/2402916
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Dermal Mesenchymal Stem Cell-Derived Exosomes Accelerate Cutaneous Wound Healing by Activating Notch Signaling

Abstract: Fetal dermal mesenchymal stem cells (FDMSCs), isolated from fetal skin, are serving as a novel MSC candidate with great potential in regenerative medicine. More recently, the paracrine actions, especially MSC-derived exosomes, are being focused on the vital role in MSC-based cellular therapy. This study was to evaluate the therapeutic potential of exosomes secreted by FDMSCs in normal wound healing. First, the in vivo study indicated that FDMSC exosomes could accelerate wound closure in a mouse full-thickness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
96
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 49 publications
4
96
0
Order By: Relevance
“…These authors have shown that the effects of such EV on fibroblasts were mediated by activation of the Notch pathway. That was a consequence of the EV carrying the Notch ligand, known as jagged 1 (JAG-1) (Wang et al, 2019b). That is in agreement with the important roles assigned to the Notch-signaling pathway in wound healing (Chigurupati et al, 2007;Shi et al, 2015).…”
Section: Fibroblastssupporting
confidence: 69%
See 2 more Smart Citations
“…These authors have shown that the effects of such EV on fibroblasts were mediated by activation of the Notch pathway. That was a consequence of the EV carrying the Notch ligand, known as jagged 1 (JAG-1) (Wang et al, 2019b). That is in agreement with the important roles assigned to the Notch-signaling pathway in wound healing (Chigurupati et al, 2007;Shi et al, 2015).…”
Section: Fibroblastssupporting
confidence: 69%
“…Besides, they increased the proliferation and migration of dermal fibroblasts in vitro. In addition, they induced the expression of genes encoding ECM proteins, such as collagen type I and III, fibronectin 1, elastin, and alpha-smooth muscle actin (a-SMA) (Wang et al, 2019b). These authors have shown that the effects of such EV on fibroblasts were mediated by activation of the Notch pathway.…”
Section: Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that the features of fetal tissue cells facilitate engraftment in vivo and may provide preferred effects against diseases di cult to treat [7]. Since 1928, hundreds of clinical trials using various types of fetal transplants have been performed worldwide [8][9][10].Moreover, recently studies have been demonstrated that human fetal stem cells have a great growth promoting potential, which bene ted to the tissue regeneration and cell therapy [11,12]. In comparison to other mesenchymal stem cell (MSCs), fetal stem cells (FSCs) are easier to culture and more readily proliferate, and less likely to be rejected by transplant recipients, as these cells are less antigenic [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since 1928, hundreds of clinical trials using various types of fetal transplants have been performed worldwide [8][9][10]. Moreover, recent studies have been demonstrated that human fetal stem cells have a signi cant growth promoting potential, which bene ted to tissue regeneration and cell therapy [11,12]. In comparison to other mesenchymal stem cells (MSCs), fetal stem cells (FSCs) are easier to culture and more readily proliferate, and less likely to be rejected by transplant recipients, as these cells are less antigenic [8].…”
Section: Introductionmentioning
confidence: 99%